Evaluation of Effectiveness of Gugguladi Dhoopana as an Adjuvant in Postoperative Management of Fistula-in-ano: A Series of Three cases - Sakshi Ghugal; Sheetal Asutkar; Shubham Bobade; Yogesh Yadav (Journal of Clinical and Diagnostic Research)
Dhoopana Karma is one of the traditional Ayurvedic treatments for fumigation, which aids in enhancing wound healing and preventing infections within wounds following surgeries. This treatment can be administered through the fumes produced by herbal preparations, based on their theoretically potent antimicrobial and anti-inflammatory actions, as well as their wound healing properties. Dhoopana Karma utilises the formulation Gugguladi Dhoopana Dravya, which includes Guggul, Nimba, and Sarjaras. These substances are well-known for their tissue regeneration and infection-controlling activities. Hereby, the authors present a case series of three male patients and present study was aimed to determine whether Dhoopana Karma is effective in the treatment of postoperative anal fistula. The present condition requires prolonged care and is often associated with infections and poor healing. Three patients diagnosed with complex anal fistula underwent partial fistulectomy accompanied by Ksharsutra (medicated seton) ligation, followed by daily Dhoopana Karma with Gugguladi Dhoopana Dravya for 10 days. Each session lasted 10 minutes. Pain, wound bed condition, odour, discharge, granulation tissue, and itching were monitored regularly. The fumigation process involved in Dhoopana Karma helps to stimulate blood circulation, promotes the removal of toxins, and reduces inflammation at the wound site. Dhoopana can be utilised as an alternative to the modern concept of sterilisation and has multiple applications in wound management. All cases showed dramatic improvement, with significant reductions in pain, discharge, and odour, along with enhanced granulation tissue formation during the 30-day follow-up period. Dhoopana Karma with Gugguladi Dhoopana Dravya appears to be a beneficial adjuvant treatment for the postoperative management of anal fistula, leading to early recovery and more efficient wound healing.